Mindfulness-based (non-contact) boxing therapy (MBBT) for depression and anxiety: A feasibility study - Johny Bozdarov; Brett D.M. Jones; Madeha Umer; Daniel M. Blumberger; Ishrat M. Husain (PLoS ONE, 2025)
Objectives Mindfulness-Based (non-contact) Boxing Therapy (MBBT) is a novel intervention designed to empower and promote self-agency through behavioral interventions, while reducing barriers to exercise for individuals with mental disorders. MBBT is an instructor-led, manualized, non-contact boxing group-exercise program (delivered in 90 min sessions, twice a week, over 10 weeks) that blends principles of mindfulness, meditation and group therapy. The current study tested the acceptability and feasibility of delivering MBBT to adults with major depressive disorder (MDD) or generalized anxiety disorder (GAD). Methods Nine adult outpatients with MDD or GAD were recruited from a psychiatric outpatient clinic in Toronto, Canada in a 10-week feasibility trial of MBBT using a pre-post design. Feasibility was assessed through recruitment and retention rates, while acceptability was assessed through the CSQ-8, and self-questionnaires. Secondary clinical outcomes included the PHQ-9, GAD-7, K10, CGI, and MAAS. Trial registry: ISRCTN23023309. Results Eight participants (5 female, 3 male) were included in the final analysis. Results indicated a high user retention (89%), attendance (84%), and satisfaction (98%). The study observed a statistically significant mean percent reduction in depression (54%), anxiety (51%) and distress (36%), alongside a mean percent increase in mindfulness (79%). Post intervention qualitative feedback from participants revealed themes of inclusivity and accessibility, cathartic release and control of emotions, improved self-esteem and confidence, self-agency, community, and trust in leadership. Conclusions Given the limitation of the study, MBBT appeared to be feasible and acceptable as an exercise/behavioural intervention. Further well-designed randomized clinical trials are warranted to confirm the clinical benefits of MBBT.